2019
DOI: 10.1029/2018rs006687
|View full text |Cite
|
Sign up to set email alerts
|

Noise Suppression Method for Magnetic Resonance Sounding Signals Based on Double Singular Value Decomposition

Abstract: Magnetic resonance sounding (MRS) is a geophysical method that directly detects, evaluates, and monitors groundwater resource. The amplitude of the MRS signal detected by the instrument is on the order of nanovolts, resulting in very sensitive to environmental noise and power line harmonics. The singular value decomposition (SVD) method separates the signal from the noise based on the different component contributions to the singular values between the MRS signal and noise. In this paper, we propose a noise su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It was reported that the key to SVD denoising was the selection of the de-noised order [29]; a lower order could result in missing and lost original signal information. Additionally, a higher order could lead to the retention of overmuch noise information, which pollutes the noise and could not realize denoising.…”
Section: Reconstructed Order Determinationmentioning
confidence: 99%
“…It was reported that the key to SVD denoising was the selection of the de-noised order [29]; a lower order could result in missing and lost original signal information. Additionally, a higher order could lead to the retention of overmuch noise information, which pollutes the noise and could not realize denoising.…”
Section: Reconstructed Order Determinationmentioning
confidence: 99%
“…Inverse problems are often ill posed, and regularisation methods have emerged as pivotal for addressing these challenges. Key regularisation techniques include the Tikhonov regularization method (TRM) [16,17], Truncated Singular Value Decomposition (TSVD) [18], and Damped Singular Value Decomposition (DSVD) [19], along with a variety of iterative regularisation approaches, such as the Landweber iteration [20], the Conjugate Gradient iteration [21], and the Least Squares QR (LSQR) iteration method [10].…”
Section: Introductionmentioning
confidence: 99%